Psikologi Maryam dalam Al-Qur’an - Fatimah, Fatimah; Hasiah, Hasiah (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
The Qur'an provides motivation or encouragement for humans to think about their personality, about the extraordinary creation of Allah SWT with all the uniqueness in every event. This is the impetus for humans to conduct research on the soul and its secrets. As contained in the letter Ali-Imran verses 42-48 regarding Psychology Maryam faced extraordinary events during the moments of the birth of the prophet Isa as. The formulation of the problem in this study is how Maryam's character is immortalized in the Qur'an, and how is Maryam's psychology in the Qur'an based on the thematic interpretation approach to Q.S. Ali-Imran: 42-48). The type of research used in this thesis is library research. Sources of data used in this thesis are in the form of primary library materials such as the Qur'an and interpretation books such as Tafsir Al-Azhar. The secondary data sources include commentaries, books and scientific papers related to research. The results of the study indicate that the character Maryam enshrined in the Qur'an is a woman chosen by Allah SWT because she comes from a good lineage, worships a lot, zuhud, is noble and purified from various forms of doubt and bad character. As for Maryam's psychology, based on the explanations of several commentators, namely Maryam has a good and tough personality, it can be seen from Maryam's obedient attitude and does not deny the news of her pregnancy which was conveyed through the angel Gabriel, even though Maryam is not married and has never been touched by any man. The good personality embedded in Maryam comes from a very conducive childhood background, she was born to pious parents and was raised by a prophet, namely the prophet Zakaria as.